2023
DOI: 10.3389/fpls.2023.1146577
|View full text |Cite
|
Sign up to set email alerts
|

Chemical priming of plant defense responses to pathogen attacks

Abstract: Plants can acquire an improved resistance against pathogen attacks by exogenous application of natural or artificial compounds. In a process called chemical priming, application of these compounds causes earlier, faster and/or stronger responses to pathogen attacks. The primed defense may persist over a stress-free time (lag phase) and may be expressed also in plant organs that have not been directly treated with the compound. This review summarizes the current knowledge on the signaling pathways involved in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 166 publications
1
8
0
Order By: Relevance
“…Systemic acquired resistance occurs in disposal plant parts following infection by the pathogen in the localized core of infection. This process is controlled by a signaling pathway depending upon the regulatory protein NPR1 and salicylic acid accumulation (Hönig et al, 2023). The enhanced WRKY6 induction is consistent with enhancement of our related marker genes R1, PR5, and RGA29, basically resistant to FOC for comparing and con rming the results of our research (Chand et The resistant onion ''Saba'' and ''Saba' -HS' showed the highest accumulation of PR5 transcripts at all the course times in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Systemic acquired resistance occurs in disposal plant parts following infection by the pathogen in the localized core of infection. This process is controlled by a signaling pathway depending upon the regulatory protein NPR1 and salicylic acid accumulation (Hönig et al, 2023). The enhanced WRKY6 induction is consistent with enhancement of our related marker genes R1, PR5, and RGA29, basically resistant to FOC for comparing and con rming the results of our research (Chand et The resistant onion ''Saba'' and ''Saba' -HS' showed the highest accumulation of PR5 transcripts at all the course times in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The alarming increase in the human population, and the ever-increasing crop demand led to intensive agricultural operations, which enhance the pathogen attack intensity (Soheili et al, 2023; Gholamaliyan et al, 2021). Chemical method of disease control via chemical pesticides usually affects adversely in nutrient cycles, natural bio-control factors, and bene cial organisms (Haghani et al, 2014;Kasem et al, 2019;Hönig et al, 2023). Thus, the preferred choice is the establishment of resistance in the target crops via genetic engineering technology (Forghani et al, 2021;Filyushin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In this present study, 21-day old leaves or roots were mechanically wounded and immediately subjected to treatment or mock. Since TaCAD-A1 and TaCAD-D1 were detectable without vacuum in ltration or untreated overnight incubation, we postulate that the experimental design of the RNAseq PAMP assay may have skewed the resulting data by priming the tested tissue to produce a stress response (91,92). The differences between the RNAseq and the qRT-PCR assays may also be explained by the high sequence homology present among the class I TaCAD homoeolog cDNA sequences (Supplementary Table S7).…”
Section: Differential Expression Of Class I Tacads May Contribute To ...mentioning
confidence: 99%
“… 1 , 2 A diverse set of stimuli has been shown for being effective in priming the plant immune system against pathogens. 3 , 4 This includes abiotic changes and pretreatments with altered environmental conditions as a consequence of activated cross-tolerance. Several short (1.5 h) and repetitive cold (4°C) or heat (38°C) treatments increase the resistance of Arabidopsis thaliana (Arabidopsis) against the hemi-biotrophic, virulent pathogen Pseudomonas syringae pv.…”
Section: Short Communicationmentioning
confidence: 99%